HUBUNGAN GERAKAN LITERASI SEKOLAH DAN MINAT BACA DENGAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS VIII SMP NEGERI 1 SUNGAI APIT - Novirna, Eka Pani; Auzar, Auzar; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstact: This study to determine whether there is a positive and significant relationship between the School Literacy Movement and reading interest with the results of learning Indonesian. This research is a quantitative study with a type of correlation. The subjects in this study were eighth grade students of SMPN 1 Sungai Apit with a total sample of 83 students. The research instrument was in the form of a questionnaire about the School Literacy Movement and reading interest and report cards in Indonesian. Test the validity of the instrument calculated using the Product Moment correlation formula from Karl Pearson, and the instrument reliability test was calculated using the Cronbach Alpha formula. Analysis prerequisite test consisted of normality test, linearity test and homogeneity test. Hypothesis testing is done by Product Moment correlation analysis to test the first and second hypotheses. The results showed that: (1) there was a positive and significant relationship between the School Literacy Movement and the learning outcomes of Indonesian eighth grade students of SMPN 1 Sungai Apit, this was indicated by r 0.374 greater than rtable 0.261 and the calculated coefficient 0, 00 is less than the price of Î± 0.05. (2) There is a positive and significant relationship between reading interest and learning outcomes of class VIII SMPN 1 Sungai Apit, this is indicated by rcount 0.435 greater than rtable 0.261 and the calculated coefficient value is 0.00 less than the price of Î± 0 , 05. Key Words: School Literacy Movement, reading interest, learning outcomes